Adsorption of N, He and Ne on CGe nanoribbons for sensing and optoelectronic applications - Hoang Van Ngoc (Royal Society Open Science, 2024)
Research into nanomaterials yields numerous exceptional applications in contemporary science and technology. The subject of this investigation is a one-dimensional nanostructure, six atoms wide, featuring hydrogen-functionalized edges. The theoretical foundation of this study relies on Density Functional Theory (DFT) and is executed through the utilization of the Vienna Ab initio Simulation Package (VASP). The outcomes demonstrate the stability of adsorption configurations, along with the preservation of a hexagonal honeycomb lattice. The pristine configuration, characterized by a wide bandgap, is well-suited for optoelectronic applications, whereas adsorption configurations find their application in gas sensing. Nitrogen (N) adsorption transforms the semiconducting system into a semimetallic one, with the spin-up state showing semiconductor characteristics and the spin-down state exhibiting metallic attributes. The intricate multi-orbital hybridization is explored through the analysis of partial states. While the pristine system remains non-magnetic, N adsorption introduces a magnetic moment of 0.588 μB. The examination of charge density differences indicates a significant charge transfer from N to the CGe substrate surface. Optical properties are systematically investigated, encompassing the dielectric function, absorption coefficient and electron–hole density. Notably, the real part of the dielectric function exhibits negative values, a result that holds promise for future communication applications.